Analisis Risiko Kesehatan Lingkungan Pajanan Karbon Monoksida (CO) Pada Pedagang Sate di Palembang - Dini arista putri; Amrina Rosyada; Widya Lionita; Desri Maulina sari; Fison Hepiman; Dian Islamiati (STIKes Hang Tuah Pekanbaru, 2022)
Level of pollutants in the air that humans breathe every day will impact health for now or future. The occupational risk of satay traders who are exposed to carbon monoxide from grilling food using charcoal is often not realized. The aims of this study are to measure carbon monoxide levels exposed to satay traders in Palembang and examine the magnitude of the risk in several future time periods. This study is used a quantitative design with environmental health’s risk analysis approach. Assessment of carbon monoxide is used Carbon Monoxide Meter. Respondents were selected through the purposive sampling technique by as many as 58 persons. They were selected by criteria: used charcoal as fuel and were the street vendor. Carbon monoxide exposure was in the range of 12.3 – 163 mg/m3. The intake value is influenced by the concentration of the risk agent, rate of intake, as well as duration, frequency, and time of exposure. The results showed real-time intake value was 20,62 while the lifetime intake was 78,60. Realtime RQ calculated CO exposure will be risky if exposed within a period of 30 years. However, it was found that almost 40 percent of respondents had risk based on real-time RQ values with each duration. Analysis of CO exposure’s risk on satay traders is predicted to occur at the 10th year of exposure, which is influenced by the increasing exposure time. For reducing the level of CO exposure, satay traders are advised to use personal protective equipment such as masks and may consider using smokeless food grills/electric grills.